Penerapan Model Mind Mapping Berbantuan Media Pohon Ajaib Pada Siswa Tema 6 Cita-Citaku Kelas IV Sekolah Dasar - Sholekhah, Khilyatus; Roysa, Mila; Masfuah, Siti (Universitas Muria Kudus, 2019)
This study aims to describe the application of the Mind Mapping model assisted by magic tree media in increasing learning motivation, students' critical thinking and teacher skills. Theme 6 My Idea for Class IV Elementary School. Data collection techniques used were observation, interviews, documentation and tests. Data analysis in this study consisted of quantitative and qualitative. The results showed an increase in students' learning motivation by using the observation results of the first cycle with an average of 65 with criteria needing guidance, experiencing an increase in the second cycle that is 79 with good criteria, besides learning motivation was also seen from the questionnaire sheet with results 88 with good criteria. Critical thinking of students in the first cycle reaches an average of 65 with the criteria needing guidance, experiencing an increase in the second cycle that is equal to 77 with sufficient criteria.Teacher's skills also experienced an increase in cycle I reaching 88 with good criteria and in cycle II it reached an average of 97 with very good criteria.This proves that the application of the Mind Mapping model assisted by magical tree media can increase motivation to learn, critical thinking of students and teacher skills.Theme 6